Theories of the policity process - Sabatier, Paul A (Colorado: Westview press, 1999)
Este documento contiene las siguientes partes: 1. introduction. part 2. alternative views of the role rationality in the pilicy process. 3. framewoks focusing on policy change over fair long periods. 4. frameworks comparing policies across a large number of political systems. 5. onclusions
Keywords: Ciencias Políticas; Planteamiento